2013
DOI: 10.1016/j.physletb.2013.02.051
|View full text |Cite
|
Sign up to set email alerts
|

NLO QCD corrections to the production of Higgs plus two jets at the LHC

Abstract: We present the calculation of the NLO QCD corrections to the associated production of a Higgs boson and two jets, in the infinite top-mass limit. We discuss the technical details of the computation and we show the numerical impact of the radiative corrections on several observables at the LHC. The results are obtained by using a fully automated framework for fixed order NLO QCD calculations based on the interplay of the packages GoSam and Sherpa. The evaluation of the virtual corrections constitutes an applica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 72 publications
1
61
0
Order By: Relevance
“…Several analyses [33][34][35] demonstrated that the φ jj -correlations survive with minimal modifications if the hard radiation is separated from the parton shower and the hadronization effects. Similar conclusions were obtained by a parton level calculation of the GF induced Higgs plus two jet production process at NLO [36,37] within the framework of the heavy top-quark effective theory.…”
Section: Introductionsupporting
confidence: 84%
“…Several analyses [33][34][35] demonstrated that the φ jj -correlations survive with minimal modifications if the hard radiation is separated from the parton shower and the hadronization effects. Similar conclusions were obtained by a parton level calculation of the GF induced Higgs plus two jet production process at NLO [36,37] within the framework of the heavy top-quark effective theory.…”
Section: Introductionsupporting
confidence: 84%
“…[7,8] with the results of the fiducial measurements is also not possible. When the Higgs boson is produced in association with two and three jets, the NLO QCD computations provide the state-of-the-art results [11][12][13][14]. In those NLO QCD computations decays of the Higgs bosons are routinely taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…This higher-rank decomposition has been used for the computation of NLO corrections to Higgs-boson production in association with two [52] and three [27,53] jets. Other libraries which implement the reduction of higher-rank integrals are Xsamurai [54], which extends the more traditional integrand reduction algorithm of Samurai, and Golem95 [55][56][57].…”
Section: Discussionmentioning
confidence: 99%